Penerapan Asas Legalitas dalam Kasus Penanganan Pencabulan Anak di Bawah Umum - Warjiyati, Sri (Al-Jinayah : Jurnal Hukum Pidana Islam, 2019)
Cases of crime in children often occur, even the number of crimes is increasing year by year. With the frequent crimes that occur in children, it requires firm action and protection from KPAI as an institution for the protection of children. Given the form of abuse is a violation of children's rights and can not be justified whatever the reason, both in terms of moral, moral and religious. The children have the right to be protected for their welfare, because the children are a vulnerable group. With the existence of laws and regulations related to children's rights, it can protect children in crime. In addition, the crime against children can provide a deterrent effect. In terms of criminal law, the offender of crimes against the children can be subject to the law as well. Seeing the number of victims of molestation, of course the offender's can be punished according to the principle of legality, namely the principle that no acts are prohibited and threatened with criminal offenses if not determined in advance in legislation. In Article 82, the perpetrators of crimes against children are subject to a maximum sentence of 15 years and a minimum of 3 years in prison with a maximum fine of 300,000,000.00 and at least 60,000,000.00. Whereas in Islamic criminal law the offender's are stoned to death, flogged a hundred times.